2008
DOI: 10.1021/jp801247d
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study on the Decomposition of Formic Acid Catalyzed by (H2O)x, x = 0−3: Comparison of the Gas-Phase and Aqueous-Phase Results

Abstract: The mechanisms for the water-catalyzed decomposition of formic acid in the gas phase and aqueous phase have been studied by the high-level G2M method. Water plays an important role in the reduction of activation energies on both dehydration and decarboxylation. It was found that the dehydration is the main channel in the gas phase without any water, while the decarboxylation becomes the dominant one with water catalyzed in the gas phase and aqueous phase. The kinetics has been studied by the microcanonical RRK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Keywords: biomass • formic acid • high temperature and pressure water • reactor wall • reduction the dehydration reactions. The literature provides many studies on this topic, [20][21][22][23][24][25] taking into account the possible effects of density, surface-catalyzed reactions, and ionic or radical mechanisms. However, although all of the experimental results have confirmed that the decarboxylation is the main reaction path under supercritical or near-supercritical conditions, several inconsistencies regarding the mechanism of formic acid decomposition in the presence of water have not been fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Keywords: biomass • formic acid • high temperature and pressure water • reactor wall • reduction the dehydration reactions. The literature provides many studies on this topic, [20][21][22][23][24][25] taking into account the possible effects of density, surface-catalyzed reactions, and ionic or radical mechanisms. However, although all of the experimental results have confirmed that the decarboxylation is the main reaction path under supercritical or near-supercritical conditions, several inconsistencies regarding the mechanism of formic acid decomposition in the presence of water have not been fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…The role of hydrogen bonded molecular complexes on the kinetics and dynamics of gas-phase free radical reactions has been the focus of interest of both experimental and theoretical investigations, [1][2][3][4][5][6], and several articles have been published involving possible one-molecule catalysis in reactions of OH radicals with organic volatile compounds [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…64 (formamide and HCN formation) and in ref. 65 (HCOOH formation). The transition states and barrier heights in the latter works are quite similar to our results at T = 650 K, considering the different treatment of temperature (approximations based on harmonic vibrations in the literature versus moleculardynamics in our case) and the different quantum-mechanical approximations [B3LYP, G2M, MP2, and CCSD(T) in the literature versus density functional theory-Perdew-Burke-Ernzerhof (DFT-PBE) in our case].…”
Section: Resultsmentioning
confidence: 99%